Modern Obesity Pharmacotherapy: Weighing Cardiovascular Risk and Benefit. Issue 11 (15th September 2014) - Cunningham, Jonathan W.; Wiviott, Stephen D.
Abstract Obesity is a major correlate of cardiovascular disease. Weight loss improves cardiovascular risk factors and has the potential to improve outcomes. Two drugs, phentermine plus topiramate and lorcaserin, have recently been approved by the US Food and Drug Administration for the indication of obesity; a third, bupropion plus naltrexone, is under consideration for approval. In clinical trials, these drugs cause weight loss and improve glucose tolerance, lipid profile, and, with the exception of bupropion plus naltrexone, blood pressure. However, their effect on cardiovascular outcomes is unknown. In defining appropriate roles for these drugs in preventive cardiology, it is important to remember the checkered history of drugs for obesity. New weight‐loss drugs share the serotonergic and sympathomimetic mechanisms that proved harmful in the cases of Fen‐Phen and sibutramine, respectively, albeit with significant differences. Given these risks, randomized cardiovascular outcomes trials are needed to establish the safety, and potential benefit, of these drugs. This review will discuss the history of pharmacotherapy for obesity, existing efficacy and safety data for the novel weight‐loss drugs, and issues in the design of postapproval clinical trials.